Influence of ultimate pH on bovine meat tenderness during ageing - Patarata, Luis (1999)
The aim of this work was to evaluate the influence of ultimate pH and ageing at 2+/-2ºC on the tenderness of beef. The longissimus thoracis et lumborum from 23 young bulls excised at 28 hours post mortem were grouped into : Normal (pH 5.5 to 5.8) moderate DFD (5.8<pH<6.2) and DFD (pH 6.2 to 6.7). The toughness measured by Warner-Bratzler shear force (WBSF) and by sensory evaluation, were significantly (P<0.05) lower in the DFD group than in the Normal one and a significant (P<0.001) linear relationship was found between the ultimate pH and the tenderness evaluated by both methods. The myofibrillar protein solubility (MPS) extracted at pH 7.0 was significantly higher in the DFD group at all post mortem times whereas for myofibrillar fragmentation index (MFI) higher values (P<0.05) were only found at day 1, particularly in the DFD group. In all 3 groups toughness decreased (P<0.05) from 1 to 6 days, with no further decrease at 13 days. This decrease in thougness was concomitant with the increase of MFI observed in all pH groups. Collagen solubility in all 3 groups was not affected by ageing. No significant (P>0.05) differences in soluble collagen and myofibrillar protein solubility (MPS) extracted at pH 5.5 were found between the pH groups on any of the storage days. The tenderness evaluated by both methods was significantly (P<0.05) related with MFI, MPS at pH 7.0, cooking loss and juiciness. Total and soluble collagen, sarcomere length, intramuscular fat and MPS at pH 5.5 were not significantly (P>0.05) related with the tenderness of the meat.